The Effect of Overshoot on the Performance of the 4G LTE Network in the East Sawahan Region - Yuhanef, Afrizal; Yusnita, Sri; Gusvita, Dina (Brilliance: Research of Artificial Intelligence, 2024)
Network interference such as overshoot can affect differences in signal quality and strength on cellular networks. Overshoot is a situation where the network power coverage exceeds the initial planning limit, causing users to be served by cells that are further away than the closest cells. This research aims to deal with problems that arise due to overshoot in the East Sawahan area. The research was conducted using the drivetest method in East Sawahan, Padang. The software used is TEMS Pocket for collecting measurement data and TEMS Discovery software for processing drivetest result data. Network performance is seen from the RSRP, SINR and PCI parameters. In this problem, network performance was improved using Atoll software. With the antenna tilting method which was previously 0? increased to 6?, the improvement results show that after making changes to network performance the signal quality meets the results of the KPI standards.